The clustering and segmentation of customers and products in the multi-channel sales of B2B e-commerce trading companies - Bąska, Mateusz (Klastrowanie i segmentacja klientów i produktów w sprzedaży wielokanałowej firm handlowych działających w e-commerce w segmencie B2B, 2021)
Given the progressive growth of e-commerce sales and the increasing interest in large-channel sales of business-to-business (B2B) trading companies among researchers and practitioners, the aim of this article was to identify the needs related to clustering and segmentation in B2B trading companies, as well as the techniques currently in use. Issues related to clustering and customer and product segmentation were explored and the most promising research areas for the nearest future identified. The article outlines the main techniques for clustering and segmenting customers and products, and identifies potential areas for further research. From a managerial perspective, the article is useful for companies entering the domain of multi-channel sales to guide their future efforts on methods to increase the value of customer purchases.
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 2 (60), s. 14-26
Keywords: clustering; segmentation; e-commerce; omnichannel; systematic review; klastrowanie; segmentacja; przegląd literatury